PERAN NAHDLATUL ULAMA DALAM PENDIDIKAN POLITIK DI KABUPATEN MAJENE - Muhammad, Muhammad; Farhanuddin, Farhanuddin (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2017)
In playing their political roles, each social and religious organization in Indonesia has their own values and ideals to apply and to maximize within the context of their socio-political life in the country. Nahdhatul Ulama (NU) of Majene Regency has inevitably been in this circumstance. This article is intended to observe the role of Nahdhatul Ulama in Majene Regency played for political education. The research was qualitatively conducted in Majene and descriptively analyzed. The samples were purposively chosen among the Syuriah and Tanfidziah board of this local Nahdhatul Ulama. This is due to the fact that the dynamic of Nahdhatul Ulama in Majene is centralized among the roles of the ulamas themselves. The meaning of politics for the majority of NU members in Majene has been reduced to something negative. This in turn needs the language of religious figures to provide the right meaning. In this case, the political language of the ulamas of NU is needed in order to convey the message of political education which is in line with the values and ideals of NU itself. The deliverance of such message in the language of NU influential figures in the area is believed to be rightly conveyed and easily accepted by its members.